The Values of Local Wisdom in the Bretes (Seven-Month) Tradition among the Community of Jeringo Village, Gunungsari District, West Lombok Regency - Harsandi, Muhammad Ladoni; Hilmi, Muhamad Zoher; Ningsih, Dewi Puspita; Rahmadi, Didin Septa (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the values of local wisdom embedded in the Bretes (seven-month) tradition in the community of Jeringo Village, Gunungsari District, West Lombok Regency, as well as the strategies employed to preserve it. A qualitative approach with a case study design was used, involving observations, in-depth interviews, and documentation as data collection techniques. The findings indicate that the Bretes tradition embodies a wide range of local wisdom values, including mutual cooperation, togetherness, social solidarity, religiosity, gratitude, charity, kinship, care, and educational significance. This tradition not only reinforces cultural identity and social cohesion but also serves as a medium for moral and spiritual education for younger generations. Preservation strategies include intergenerational transmission, active community participation, integration of religious and social values, and documentation and dissemination to youth. The findings underscore the relevance of the Bretes tradition as a medium for value transfer, strengthening solidarity, and integrating customary practices with religion, highlighting the importance of preserving local wisdom amid the challenges of modernization. The study contributes theoretically to understanding the role of local wisdom in shaping community character and practically as a reference for the development of cultural preservation programs.